CHRISTIAN SUBMITTING TO ROMAN AUTHORITY ACCORDING TO ROMANS 13:1-7 - Tofană, Stelian (Sacra scripta, 2015)
This study analyses a text from Romans 13,1-7 where the Apostle Paul presents six reasons for the Christian submission and obedience to the civil Roman authority at that time. Taking into account that the Roman Persecutions against to Christians have already made a lot of victims among them, Paul’s exhortations to Roman Christians urging them to be obedient to secular authority, seemed to be extremely courageous. Paul argues his advices by affirming that governing authority that exists is established by God and it is, therefore, his “ministry” in the world rewarding the good deeds and punishing the wrong ones. According to this perspective the Christians motive for submission to the civil authority is not “the fear”, but rather “the conscience” and “the love”. Rom 13,1-7 constitutes, therefore, the key text of the entire New Testament on the subject of Christian’s obedience and submission towards the State’s civil authority.